2016
DOI: 10.2196/jmir.6342
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Evaluating Respondent Attrition in Web-Based Surveys

Abstract: BackgroundElectronic surveys are convenient, cost effective, and increasingly popular tools for collecting information. While the online platform allows researchers to recruit and enroll more participants, there is an increased risk of participant dropout in Web-based research. Often, these dropout trends are simply reported, adjusted for, or ignored altogether.ObjectiveTo propose a conceptual framework that analyzes respondent attrition and demonstrates the utility of these methods with existing survey data.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 26 publications
(40 reference statements)
1
46
0
Order By: Relevance
“…This may lead to a conceptualization of survey fatigue on a spectrum rather than as a binary outcome. The attrition approach has been previously described for Web-based surveys ( Hochheimer et al, 2016 ). More detailed analysis of step offs and straight-line answering may provide feedback for how to modify a survey to reduce the rate of fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may lead to a conceptualization of survey fatigue on a spectrum rather than as a binary outcome. The attrition approach has been previously described for Web-based surveys ( Hochheimer et al, 2016 ). More detailed analysis of step offs and straight-line answering may provide feedback for how to modify a survey to reduce the rate of fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Respondent fatigue, also known as survey fatigue, is a common problem in the collection of survey data ( Whelan, 2008 ; Ben-Nun, 2008 ). It refers to the situation in which respondents give less thoughtful answers to questions in the later parts of a survey, or prematurely terminate participation ( Whelan, 2008 ; Ben-Nun, 2008 ; Hochheimer et al, 2016 ). This may be detected when there is straight-line answering, where the respondent chooses e.g., the first option of a multiple choice survey for multiple question in a row.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed analysis of module attrition has been previously reported. 44 When the module was used, paradata indicated that 291 patients ( Note: Given the large sample size, all differences across groups (noncompleters, completers, and nonstarters) were statistically significant (P <.001) with the exception of Medicaid insurance type.…”
Section: Decision Module Usementioning
confidence: 99%
“…Those who we were unable to retrospectively follow up fell into attrition. In many longitudinal studies, observations across waves can be missing for various reasons, and the attrition rate for web-based surveys is especially high (25). Another reason for our high attrition rate may be that we use the forced response mode; people will stop working on the survey if they are asked questions they do not wish to answer (26), although some of our questions included a "no answer" option.…”
Section: Sampling and Data Collectionmentioning
confidence: 99%